A Discussion of "Disorders of Temporality and The Subjective Experience of Time: Unresponsive Objects and the Vacuity of the Future" by Stephen Seligman. Issue 2 (3rd March 2016) - Shane, Estelle
Abstract : In this review of Stephen Seligman's contribution to the literature on disorders of temporality, the patient's ordinary and extraordinary experiences of time in the clinical situation, the reviewer provides both theoretical confirmation and clinical illustration in support of the author's arguments. Infant research, nonlinear dynamic systems theory, and especially a brain-based psychoanalytic perspective taken from the work of Gerald Edelman are introduced to facilitate understanding of memory in general and the second of Seligman's disorders of temporality in particular. Edelman's formulation on the biological evolution of consciousness affords a means to comprehend how the phenomenon of dissociation emerges spontaneously in the clinical situation that matches and offers an explanation Seligman's own understanding.